Treatment Strategy for Unruptured Intracranial Aneurysm in Elderly Patients: Coiling, Clipping, or Conservative?. Issue 6 (June 2019) - Yang, H.; Jiang, H.; Ni, W.; Leng, B.; Bin, X.; Chen, G.; Tian, Y.; Gu, Y.
An increasing number of unruptured intracranial aneurysms (UIAs) has been discovered in elderly patients in recent years, but the optimal treatment strategy for these patients remains controversial. We report our six-year experience treating UIAs in elderly patients (≥ 70 years old). A retrospective review was conducted of elderly patients who harbored UIAs treated by conservative observation, microsurgical clipping, or endovascular coiling between January 2009 and December 2014. The patients' clinical and imaging information was recorded. Treating methods, procedure-related complications, imaging results, and clinical outcomes were analyzed. A total of 141 consecutive elderly patients with 166 UIAs were enrolled in our study. In all, 64 patients with 79 aneurysms were treated with coiling, and 14 patients with 14 aneurysms were treated with clipping. The remaining 63 patients with 73 aneurysms were placed under conservative observation. The average modified Rankin scale was 0.99 (range 0–6) in the full cohort after a mean follow-up of 50.4 months (range 0–70 months). There was no significant difference of modified Rankin scale in patients with UIAs treated by different methods. Multivariate analysis showed that age ( p =0.030) and aneurysm size ( p =0.011) were independent risk factors for unfavorable outcome of UIAs in the elderly. Patient age ( p =0.010) and aneurysm size ( p =0.020) were also significantly associated with unfavorable outcome of UIAs managed with observation initially. Our results indicated that endovascular coil embolization and clipping were both safe and effective treatment methods for UIAs in the elderly. Aggressive treatment for UIAs in elderly patients with risk factors of aneurysm rupture should be considered positively.